Regarding the problem of defining the concept of organizational principles of Ukrainian higher education quality control - V. O. Neviadovskyi (Bulletin of Kharkiv National University of Internal Affairs)
Today in the field of quality control of higher education in Ukraine there are a number of gaps and shortcomings that need to be addressed. Exploring the directions of improving the administrative and legal framework for quality control of higher education in Ukraine, it is important to pay attention to the state and prospects of development of the organizational framework for such control.